Exploring the impact of protected fat on fattening performance, carcass characteristics, fatty acid composition, and meat quality in Tuj lambs - D. Turkyilmaz; U. Dagdelen; N. Esenbuga; S. Sisik Ogras (Archives Animal Breeding)
The study assessed the impact of incorporating protected tallow fat (PF) at varying concentrations on the fattening performance, carcass characteristics, meat quality, and fattening cost of 45 lambs over a period of 73 d. The addition of 20 g per kg dry matter (DM) of PF resulted in the highest values for fattening performance and carcass characteristics (p<0.05). The pH, chemical composition, and sensory evaluation were not affected by the addition of PF, except for the cooking loss (p<0.05). The addition of PF led to an improvement in the sums of fatty acids in the longissimus thoracic muscle by reducing saturated fatty acids (SFAs) and increasing unsaturated fatty acids (UFAs). The addition of PF at a level of 20 g per kg DM positively affected (p<0.05) the ratio of oleic acid, one of the major UFAs in meat. The ratio of conjugated linoleic acid (CLA) in meat increased linearly up to 104 %, with increasing (p<0.05) levels of PF. The healthy indicators considerably improved (p<0.01). In conclusion, it is recommended to add PF at a 20 g per kg DM inclusion level to the mixed concentration to improve fattening performance, carcass characteristics, meat quality, and fatty acid composition without any economic loss.